PENGARUH LABEL HALAL, ECO-LABEL, DAN KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK LOKAL (STUDI KASUS PADA PRODUK AZZARINE) - Dini Nurhidayati; Yosy Arisandy; Rahmat Putra Ahmad Hasibuan (JSE: Jurnal Sharia Economica, 2026)
This study aims to analyze the influence of halal labels, eco-labels, and brand trust on purchasing decisions for local cosmetic products Azzarine among Generation Z consumers in Bengkulu City. This study uses a quantitative approach with primary data obtained through distributing questionnaires to Generation Z consumers who have used or purchased Azzarine products. The sampling technique used purposive sampling. The collected data were then analyzed using Statistical Package for the Social Sciences (SPSS) version 26 through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination (R²). The results show that halal labels, eco-labels, and brand trust have a positive and significant effect on purchasing decisions for local cosmetic products Azzarine. In addition, simultaneously, these three variables also have a significant effect on purchasing decisions. The R-Square value of 0.723 indicates that the variables halal labels, eco-labels, and brand trust are able to explain purchasing decisions by 72.3%, while the remaining 27.7% is influenced by other variables outside the study.